The secret of the attic - Sinykin, Sheri Cooper; Tadiello, Ed (Portland, ME : Magic Attic Press, 1995)
When four friends return a lost key to their new neighbor Ellie Goodwin, she invites them up to explore her special attic. There are costumes galore and a magic mirror that transports the girls back in time.
Keywords: Friendship -- Fiction; Fantasy; Time travel -- Fiction; Adventure stories